Evaluation of possible use of disinfectant based on chlorine dioxide in dairy plant - Rakić-Martinez Mira (Veterinarski Glasnik, 2009)
Poor sanitation of food contact surfaces has been a contributing factor in food borne disease outbreaks, especially those involving Listeria monocytogenes, Salmonella spp., Escherichia coli, Staphylococcus aureus etc. The objectives of this study were therefore to: 1. Determine the efficiency of a disinfectant based on chlorine dioxide in suspension in a closed system in a dairy plant. 2. Evaluate the possibility of disinfection of working surfaces with a disinfectant based on chlorine dioxide. In order to determine the germicidal effect of the disinfectant based on chlorine dioxide by suspension test (BSEN 1276:1997); the following test organisms were used: Listeria monocytogenes, Proteus mirabilis, Escherichia coli, Bacillus cereus, Staphylococcus aureus and Pseudomonas aeruginosa clinical isolate. The corrosive properties of the disinfectant based on chlorine dioxide were tested by IDF 077:1977 standard. The efficacy of this disinfectant was investigated in a closed system in a dairy plant. Results indicated a 100% reduction of >108 cfu/ml L. monocytogenes, E. coli, Proteus mirabilis, Pseudomonas aeruginosa, S. aureus, viable count after 1 minute of exposure to 100 ppm of the disinfectant based on chlorine dioxide and 400 ppm for Bacillus cereus. In the presence of 2% skim milk and 4 % skim milk concentrations of 200 and 250 ppm resulted in 100% reduction in numbers of the five of six test microorganisms, respectively. The spore former, Bacillus cereus is less susceptible to the disinfectant. Therefore, the efficient concentration for 100% reduction in viable count after 1 minute exposure was 500 ppm. The corrosive properties of the disinfectant were not determined. In the case of closed system disinfection in a dairy plant, reduction in viable count after 15 minute exposure to 100 ppm of disinfectant based on chlorine dioxide ranged from 80 to 100%.